2012
DOI: 10.1590/s0103-21002012000800011
|View full text |Cite
|
Sign up to set email alerts
|

Nursing intervention in insulin administration: telephone follow-up

Abstract: Objective: To analyze the competency of people with diabetes mellitus to perform the insulin administration process, before and after telephone monitoring. Methods: A quantitative, observational, longitudinal, comparative study. Participants were 26 people enrolled in the at-home capillary glycemia self-monitoring program. Data collection occurred in three phases, in January and February of 2010, for a period of 30 days for each person, by means of interview guided by a data collection instrument and an interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 12 publications
1
16
0
7
Order By: Relevance
“…However, studies concerning large values indicate a tendency toward better acceptance of the disease. (1,2,18,19) We infer that no definite tendency exists in the studied sample, but there was statistically significant improvement after the educational intervention in groups with a cognitive-behavioral approach.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, studies concerning large values indicate a tendency toward better acceptance of the disease. (1,2,18,19) We infer that no definite tendency exists in the studied sample, but there was statistically significant improvement after the educational intervention in groups with a cognitive-behavioral approach.…”
Section: Discussionmentioning
confidence: 68%
“…An inverse relation was seen between acceptance of the disease, depression, and anxiety. (2,9,15,(18)(19)(20)(21)(22) …”
Section: Discussionmentioning
confidence: 99%
“…The first study was carried out with 26 DM participants before and after telephone support consisting of four calls while in the process of insulin application. This study showed that this type of intervention strategy is effective in providing better knowledge about the application of insulin (6) . A second study was designed to verify the effect of telephone support as a strategy to favor physical activity.…”
Section: Introductionmentioning
confidence: 78%
“…It is justified to use the telephone as a data collection strategy in view of its use in health and nursing research, 11,[15][16][17][18] even making use of this resource as an intervention strategy. 19 At the rooming-in unit, the postpartum women received a folder containing a copy of the BSES-SF, so that they could use it during the telephone interview, following the reading by the research assistant. Through this strategy, the memory bias was avoided, facilitating the women's understanding of the scale items.…”
mentioning
confidence: 99%